DAMPAK PENERAPAN KURIKULUM MERDEKA TERHADAP KINERJA GURU BAHASA INDONESIA DI KELAS VII SMP NEGERI 1 POLEWALI KAPUBATEN POLEWALI MANDAR: THE IMPACT OF THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM ON THE PERFORMANCE OF INDONESIAN LANGUAGE TEACHERS IN CLASS VII OF SMP NEGERI 1 POLEWALI, POLEWALI MANDAR REGENCY - Sindi; Ramly; Sultan (Journal of Applied Linguistics and Literature, 2026)
This study aims to describe the impact of the implementation of the Independent Curriculum on the performance of Indonesian language teachers in class VII of SMP Negeri 1 Polewali, describe the readiness of Indonesian language teachers in implementing the Independent Curriculum. This type of research is qualitative research using descriptive methods. The focus of this study is the impact and readiness of Indonesian language teachers in class VII of SMP Negeri 1 Polewali in the Independent Curriculum. Data collection techniques were carried out through observation, documentation, and interviews.This study aims to describe the impact of the implementation of the Independent Curriculum (KM) on the performance and readiness of Indonesian language teachers in class VII of SMP Negeri 1 Polewali. The study used a qualitative descriptive method with data collected through observation, documentation, and interviews. The results of the study showed a positive impact of KM on teacher performance, including flexibility in developing learning, increasing creativity, understanding student needs, developing life skills, student learning motivation, comprehensive evaluation, and empowering teachers as facilitators. Teachers showed readiness in formulating learning objectives that focus on student competencies, compiling a flow of achievement-based learning objectives, designing flexible and contextual teaching modules, and understanding the concept of assessment to support competency-based learning